2011
DOI: 10.1007/s00374-011-0553-5
|View full text |Cite
|
Sign up to set email alerts
|

Emission rates of N2O and CO2 from soils with different organic matter content from three long-term fertilization experiments—a laboratory study

Abstract: Increasing organic matter stocks in soils reduce atmospheric carbon dioxide (CO 2 ), but they may also promote emissions of nitrous oxide (N 2 O) by providing substrates for nitrification and denitrification and by increasing microbial O 2 consumption. The objectives of this study were to determine the effects of fertilization history, which had resulted in different soil organic matter stocks on (1) the emission rates of N 2 O and CO 2 at a constant soil moisture content of 60% water-holding capacity, (2) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 50 publications
7
22
0
3
Order By: Relevance
“…When poultry manure was applied to soil, N 2 O fluxes were~4-fold greater than emissions from inorganic fertilisers for the whole plot area (and up to 10 times greater for the chamber area), with approximately double the N application rate for manure respectively. Other studies have also shown that the addition of animal manures result in large increases in N 2 O emissions from agricultural soils relative to background levels (Chang et al 1998;Khalil et al 2002;Rochette et al 2008;Dalal et al 2009;Jäger et al 2011;Mori and Hojito 2012). Field studies on grassland soils amended with cattle manures have recorded peak emissions of >1.6 mg m -2 h -1 (Mori and Hojito 2012), which is similar to the maximum emissions from manure treatments observed in this study of 2.3 mg m -2 h -1 .…”
Section: Discussionsupporting
confidence: 75%
“…When poultry manure was applied to soil, N 2 O fluxes were~4-fold greater than emissions from inorganic fertilisers for the whole plot area (and up to 10 times greater for the chamber area), with approximately double the N application rate for manure respectively. Other studies have also shown that the addition of animal manures result in large increases in N 2 O emissions from agricultural soils relative to background levels (Chang et al 1998;Khalil et al 2002;Rochette et al 2008;Dalal et al 2009;Jäger et al 2011;Mori and Hojito 2012). Field studies on grassland soils amended with cattle manures have recorded peak emissions of >1.6 mg m -2 h -1 (Mori and Hojito 2012), which is similar to the maximum emissions from manure treatments observed in this study of 2.3 mg m -2 h -1 .…”
Section: Discussionsupporting
confidence: 75%
“…In our study, experimental application of NH 4 NO 3 to the Hist-CaNPK soil resulted in higher N 2 O-N emission compared with the application of FYM to the Hist-CaNPK soil. Jäger et al (2011) obtained similar results in a laboratory experiment with soils from three long-term experiments in Germany. Ball et al (2004) …”
Section: Discussionsupporting
confidence: 61%
“…Além de ser fonte de alimento para microrganismos que promovem a melhoria da estrutura e arejamento, bem como manutenção da umidade e temperatura do solo, influenciando na fixação e retenção dos principais elementos requeridos pelas plantas, além de elevar a capacidade de troca catiônica (Jäger et al, 2011).…”
Section: Introductionunclassified